Population Knowledge, Attitude, and Practice Regarding Helicobacter pylori Transmission and Outcomes: A Literature Review - Driscoll, Lisa J.; Brown, Heidi E.; Harris, Robin B.; Oren, Eyal (Frontiers in Public Health, 2017)
Background: Helicobacter pylori infection is associated with the development of chronic gastritis, peptic ulcer disease, and gastric cancer. Current clinical recommendations are that H. pylori test-and-treat should be individualized based on co-morbidities and patient preferences among populations at increased risk for certain morbidities. However, knowledge, attitudes and practices regarding H. pylori among potential patient populations are largely unknown. Materials: We conducted a literature review to assess knowledge, attitudes and practices of patients or community populations around H. pylori transmission, prevention, and associated morbidity. Results: Nine studies met the inclusion criteria, all published between 1997 and 2014. Eight studies evaluated perception of H. pylori among at-risk populations, while one study evaluated perception among a general population. The studies suggest inconsistencies between the perceptions of these populations and the established understanding of knowledge, attitude and preventive practices for H. pylori among even at-risk populations. Conclusions: To adequately respond to current test-and-treat recommendations for treatment of H. pylori, general population education must be implemented, especially among at-risk populations. Further work is needed within at-risk populations in the United States to determine prevalence of H. pylori and their current knowledge if adequate prevention strategies are to be designed.